Penerapan Pendekatan Teaching at The Right Level (Tarl) untuk Meningkatkan Kemampuan Pemecahan Masalah Peserta Didik pada Materi Eksponen Kelas X SMA Negeri 2 Medan - Ainun Palihah; Pandu Prabowo Warsodirejo; Hasda Tanty (Departement of Mathematics Education, 2024)
The research on the application of the Teaching at the Right Level (TaRL) approach aims to determine students' problem-solving abilities in exponent material. This study uses a problem-based learning model. The subjects of this study were class X-10 of SMA N 2 Medan consisting of 36 students. The research method is classroom action research consisting of two cycles. Cycle I showed that 47% of class X-10 students were able to solve problems. Cycle II showed that 86% of class X-10 students were able to solve problems. This shows that the Teaching at the Right Level (TaRL) approach combined with differentiated learning is able to increase mathematical problem-solving abilities in exponent material by 39%. This shows a positive impact on mathematics learning.